Gross National Product Estimates for New Zealand; 1859 - 1939 - Rankin, Keith (School of Management Working Papers, 1991)
This paper follows from that of Gary Hawke in 1975, who used Australian and New Zealand monetary data to estimate New Zealand’s gross domestic product from 1870 to 1918, and whose data has been incorporated into international studies through the work of Paul Bairoch. It also provides an alternative set of national income estimates for the inter-war years to those published by BT Lineham in 1968. The important findings of the paper are: (i) that there is a significant relationship in the Australian data between the velocity of money and price level; (ii) that New Zealand’s GNP was significantly higher in the 1860s, 1870s and early 1880s · than Hawke’s estimates indicate; (iii) that previous gross product estimates for the inter-war period have failed to reflect the fluctuations of the New Zealand economy in the 1920s, and the extent to which it was operating below its production possibilities frontier during the Great Depression of the 1930s.